Breaking Glucose Transporter 1/Pyruvate Kinase M2 Glycolytic Loop Is Required for Cantharidin Inhibition of Metastasis in Highly Metastatic Breast Cancer - Pan, Yanhong; Zheng, Qian; Ni, Wenting; Wei, Zhonghong; Yu, Suyun; Jia, Qi; Wang, Meng; Wang, Aiyun; Chen, Wenxing; Lu, Yin (Frontiers in Pharmacology, 2019)
Aerobic glycolysis plays a decisive role in cancer growth. However, its role in cancer metastasis was rarely understood. Cantharidin a natural compound from an arthropod insect cantharis exerts potent anticancer activity. Here we found cantharidin possesses significant anti-metastatic activity on breast cancer dependent on inhibition of aerobic glycolysis. Cantharidin indicates significant inhibition on migration and invasion of breast cancer cells, angiogenesis in vitro, and inhibits breast cancer cells metastasizing to liver and lung in vivo. Subsequent results revealed that cantharidin decreases the extracellular acidification rates (ECAR) but increases the oxygen consumption rates (OCR) in high metastatic cells, leading to suppression of aerobic glycolysis. This was considered to be due to inhibiting the activity of pyruvate kinase (PK) and further blocking pyruvate kinase M2 (PKM2) translocation in nucleus. Fructose-1,6-bisphosphate (FBP) and L-cysteine can significantly reverse cantharidin inhibition on breast cancer cell migration, invasion and PKM2 translocation. Furthermore, glucose transporter 1 (GLUT1) forming a metabolic loop with PKM2 is downregulated, as well as epidermal growth factor receptor (EGFR), the regulator of the glycolytic loop. Totally, cantharidin inhibits the PKM2 nuclear translocation and breaks GLUT1/PKM2 glycolytic loop, resulting in aerobic glycolysis transformation to oxidation and subsequent reversing the metastases in breast cancer. Based on inhibiting multi signals mediated aerobic glycolysis, cantharidin could be prospectively used for prevention of metastasis in breast cancer patients.